Socially distanced, virtually connected: Faculty and resident perceptions of virtual didactics. Issue 3 (28th June 2021) - Tsyrulnik, Alina; Gottlieb, Michael; Coughlin, Ryan F.; Bod, Jessica; Della‐Giustina, David; Greenberger, Sarah; von Reinhart, Anna; Heinrich, Scott; Rotoli, Jason; Goldflam, Katja
Abstract: Background: During the COVID‐19 pandemic, emergency medicine (EM) residency programs have transitioned from traditional in‐person to virtual synchronous didactics to comply with social distancing guidelines. This study explores the perceptions of EM residents and faculty regarding this new virtual format. Methods: This was a multicenter, cross‐sectional study at five EM residencies using a mixed‐methods approach to investigate resident and faculty perceptions of virtual didactics. Institutions selected reflect different program lengths and geographic locations. Quantitative data measured on a Likert scale were summarized as percentages. Differences were calculated using Welch's t‐test and chi‐square, where p < 0.05 was significant. Open‐ended responses were analyzed qualitatively. Results: Our response rate was 64% ( n = 141) for residents and 48% ( n = 108) for faculty. Fifty‐one percent of faculty and 54% of residents felt that they were more likely to attend virtually than in person. Among residents, 77% felt that they were more likely to attend virtual conferences during vacation or elective rotations. Perceived retention of information from virtual sessions was perceived to be the same or better for 69% of residents and 58% of faculty. Residents felt that they paid more attention in the virtual format (29% vs. 26%, p = 0.037). Both groups missed the social interactions of in‐person conference (86% of faculty, 75% of residents). Respondents from both groups felt that < 20% of total didactic time should remain virtual once social distancing recommendations are lifted. Qualitative analysis revealed recommendations from residents and faculty to optimize lecture style and interactivity. Decreased commute time and ability to multitask at home increased wellness for both groups. Conclusions: While benefits of virtual didactics were acknowledged, residents and faculty missed the social interaction of in‐person conference and preferred < 20% of future didactics to be virtual. Further research should assess the difference in knowledge acquisition and retention between conference models.